House of Memories di National Museums Liverpool: un approccio integrato alle collezioni digitali per persone malate di Alzheimer - Irene Di Pietro (Museum, Materials and Discussions)
The essay aims to give an overview of the idea of “care” in museums through digital tools by presenting the case of the NML (National Museums of Liverpool) projects for people with dementia.